Phylogeography and molecular epidemiology of hepatitis C virus genotype 2 in Africa. - Markov, P; Pepin, J; Frost, E; Deslandes, S; Labbé, A; Pybus, O (2009)
Understanding the origin and nature of hepatitis C virus (HCV) genetic diversity is critical for improving treatment and vaccine design, and such diversity is the sole source of information about the virus' epidemic history prior to its identification 20 years ago. In this paper, we study the molecular epidemiology of HCV genotype 2 in its region of endemic origin, west and central Africa. Our analysis includes 56 new and highly diverse HCV isolates sampled from infected individuals in Guinea-Bissau. By combining phylogenetic, geographical and epidemiological information, we find a previously unappreciated geographical structure in the diversity of HCV genotype 2, pointing to a history of eastwards spatial spread from the west African coast to Cameroon that took place over several centuries. Molecular clock analysis dates the common ancestor of HCV in Guinea-Bissau to 1470 (1414-1582). The phylogenetic position of isolates from Madagascar and Martinique suggests a role for the historical slave trade in the global dissemination of HCV and of the epidemic subtypes 2a and 2c. Coalescent-based estimates of epidemic growth indicate a rapid 20th-century spread of HCV genotype 2 in Cameroon that is absent in Guinea-Bissau. We discuss this contrast in the context of possible parenteral HCV exposure during public-health campaigns undertaken during the colonial era.